Prevalence of dental fear among students of Hyderabad Sindh. - Shaikh, Sobia; Shazia Shabbir; Rakhshani, Abdul Qayoom; Seerat-ul-Ayesha (International Journal of Endorsing Health Science Research, 2024)
Background: Despite the advancements in making dentistry more comfortable, dental phobia remains a significant concern. Research suggests that children's dental anxiety may persist into adolescence, leading to avoidance of dental care and disruptive behavior during treatment. Early identification of children with dental fear is crucial for dental professionals to promptly employ appropriate pediatric management strategies. The study aims to assess the prevalence of dental fear among students in Hyderabad, Pakistan. Methodology: A cross-sectional study was conducted among 11- to 16-year-old male and female students in schools in Hyderabad, Pakistan. The Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) in English was utilized. The study included students in grades 6 to 8 residing in Hyderabad, with no general pathology and not on any medication. Data analysis was performed using SPSS version 25. Results: The study encompassed 295 participants, 45.1% females and 54.9% males. The percentage of participants experiencing dental fear (combining moderate and high fear) was 168 (57%), while 127 (41%) reported no dental fear. Analysis based on low to high levels of fear indicated slightly increased moderate and high fear levels in female participants (47.5% and 52%, respectively) compared to male students (36.5% and 47%, respectively). Conclusion: The study suggests the need for significant attention to preventing dental fear. School-based health policies and parents should focus on psychosocial factors associated with the fear of dental treatment, as many of these factors are preventable. Dental anxiety poses challenges not only for patients but also for dentists, occasionally complicating the successful execution of treatments.